Interface reactions among electrodes, substrates and Pb(Zr,Ti)O3-based films - Kosec, Marija (Acta chimica slovenica, 2001)
Interactions between (Pb,La)(Zr, Ti)O-3 (PLZT) thin and thick films and silicon or alumina substrates, respectively, were studied. In the case of thin films the lowering of the firing temperature inhibits the formation of secondary phases. For thick films the additional layer of PLZT between the alumina substrate and the Pt electrode improves adhesion within the PLZT thick-film heterostructures. Interactions between conductive oxides which could be used as electrodes instead of noble metals and PZT-basedmaterials are reported.
Keywords: debele plasti; interakcije; kovinski oksidi; tanke plasti